Analisis Pengaruh Return On Assets (ROA), Economic Value Added (EVA), dan Market Value Added (MVA) Terhadap Return Saham - Nainggolan, Rocky R (Universitas Sam Ratulangi, 1996)
The financial sector plays a very significant role to drive economic growth of a country. The companys performance can be seen from the financial statements that will be issued by the company periodically. The population in this study are financial services companies listed in IDX on 2010 to 2014. This study used multiple linear regression for analyze the data. The results of this study indicate that ROA, EVA and MVA simultaneously has significantly effect on Stock Return. Partially ROA has no effect on stock returns with a significant level of 0.188. While EVA and MVA has a partially significant effect on stock returns. Keywords: Return on Assets (ROA), Economic Value Added (EVA), Market Value Added (MVA), Stock Return (R), the Financial Sectors).